Mapping the forest cover of Uganda with Spot (XS) and Landsat (ETM+) images : (a case study of Bwindi Impenetrable National Park, Uganda) - Otukei, John Richard (Division of Geomatics, 2015)
Includes bibliographical references (leaves 122-124).